Pregnancy related maternal deaths at Salt River Forensic Pathology Laboratory: a 5 year retrospective study of the epidemiological data and spectrum of pathology and disease in all pregnancy related deaths at Salt River Pathology Laboratory irrespect - Khan, Akmal (Division of Forensic Medicine and Toxicology, 2014)
Includes abstract.